2016
DOI: 10.1016/j.celrep.2016.02.053
|View full text |Cite
|
Sign up to set email alerts
|

Saturated Fatty Acids Engage an IRE1α-Dependent Pathway to Activate the NLRP3 Inflammasome in Myeloid Cells

Abstract: SUMMARY Diets rich in saturated fatty acids (SFAs) produce a form of tissue inflammation driven by “metabolically activated” macrophages. We show that SFAs, when in excess, induce a unique transcriptional signature in both mouse and human macrophages that is enriched for a subset of ER stress markers, particularly IRE1α and many adaptive downstream target genes. SFAs also activate the NLRP3 inflammasome in macrophages, resulting in IL-1β secretion. We found that IRE1α mediates SFA-induced IL-1β secretion by ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
150
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(161 citation statements)
references
References 59 publications
10
150
0
1
Order By: Relevance
“…Similarly, HMGB1, the endogenous danger signal that can stimulate inflammation through activation of pattern recognition receptors (Yanai, et al, 2012) was elevated by aging in the amygdala, but was not elevated with HFD. These results are consistent with previous findings that have shown aging-induced increases, and independently, HFD-induced increases in NLRP3 and HMGB1 gene expression (Fonken, et al, 2016, Robblee, et al, 2016, Sobesky, et al, 2016). We did not find potentiated expression of these two genes when aging and HFD were combined, consistent with previous findings that also failed to show amplified expression of NLRP3 or HMGB1 when HFD was combined with LPS (Sobesky, et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, HMGB1, the endogenous danger signal that can stimulate inflammation through activation of pattern recognition receptors (Yanai, et al, 2012) was elevated by aging in the amygdala, but was not elevated with HFD. These results are consistent with previous findings that have shown aging-induced increases, and independently, HFD-induced increases in NLRP3 and HMGB1 gene expression (Fonken, et al, 2016, Robblee, et al, 2016, Sobesky, et al, 2016). We did not find potentiated expression of these two genes when aging and HFD were combined, consistent with previous findings that also failed to show amplified expression of NLRP3 or HMGB1 when HFD was combined with LPS (Sobesky, et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies showed that ER stress induces inflammasome activation through several mechanisms, including calcium mobilization and the release of reactive oxygen species from damaged mitochondria (mtROS) (44). Because earlier studies from our laboratory and the laboratories of others showed that treatment of macrophages with saturated fatty acids activates IRE1 and because these lipids specifically activated the NLRP3 inflammasome through inducing mtROS production, we sought to investigate this connection further (42,43,45). To this end, we first measured mtROS production in cells exposed to lipotoxic stress in the presence of IRE1 inhibitors.…”
Section: Resultsmentioning
confidence: 97%
“…Which lipid species mediate the activation of the UPR during lipolysis in the absence of DGAT activity is unknown. One possibility is changes in ER phospholipid composition (e.g., a higher degree of saturated fatty acid side chains), which trigger activation of the Ire1 and PERK UPR sensors (Robblee et al, 2016; Volmer and Ron, 2015; Volmer et al, 2013). …”
Section: Discussionmentioning
confidence: 99%